On a law of Indo-European word order Über ein Gesetz der indogermanischen Wortstellung - Wackernagel, Jacob (Language Science Press, 2020)
Jacob Wackernagel's 1892 essay on second-position enclitics in the Indo-European languages has long been hailed as groundbreaking in both historical and theoretical linguistics. Until now, however, it has only been available in the original German. This book provides a full translation into English, including glossed and translated examples from several early Indo-European languages and varieties and full bibliographical details of the references drawn upon, as well as a new edition of the German original. It should be of interest to researchers in historical and Indo-European linguistics and in general linguistics working on the interfaces between morphology, prosody and syntax.